Penerapan Lean Six Sigma untuk Peningkatan Kualitas Crude Palm Oil (CPO) di Pabrik Kelapa Sawit - Saputra, Arie; Hutagalung, Irna Monica; Fitriadi, Fitriadi (Universitas Teuku Umar, 2025)
This study aims to improve the quality of Crude Palm Oil (CPO) production at PT. Beurata Subur Persada through the Lean Six Sigma approach. The main problem faced by the company is the non-conformity of CPO quality to standards, especially Free Fatty Acid (FFA) levels, water content, and dirt content. To systematically identify and overcome the causes of defects, this study uses the DMAIC (Define, Measure, Analyze, Improve, Control) cycle combined with analysis tools such as Value Stream Mapping and Fishbone Diagram. The measurement results show that FFA levels are the most dominant type of defects with a DPMO value of 57,407 and a sigma level of 3.09, followed by water content and dirt content. Further analysis identified significant waste in the form of waiting, motion, defects, and overprocessing, which are caused by human, machine, method, raw material, and environmental factors. The Improve stage resulted in several recommendations for improvement such as limiting the storage time of FFB, operator training, regular machine maintenance, and using a digital recording system. The implementation of the solution showed an increase in sigma values and a decrease in the number of defects, indicating the success of the Lean Six Sigma approach in improving process capabilities. This research provides a real contribution to the application of data-based quality control methods in the palm oil industry, especially at the CPO processing level.